Wpływ działań marketingowych na wizerunek firmy Diesel Serwis Hyclak - Hyclak, Tymoteusz (My University, 2014)
Praca ta jest odpowiedzią na zagadnienia związane z wpływem działań marketingowych na firmę Diesel Serwis Hyclak. Ankieta zawarta w pracy została przeprowadzona na terenie firmy. Klienci byli proszeni o udział w ankiecie. Postawione hipotezy zostały potwierdzone tak więc można wnioskować że działania marketingowe są ważne i powinno przykładać się do nich większą uwagę. Kolejnym z przeprowadzony badań była analiza SWOT. Analiza ta pokazała potencjał firmy oraz zagrożenia płynące z rynku.

This Bachelor Thesis is a response to the issues related to the influence of marketing activities on the company Diesel Service Hyclak. The survey contained in the work was carried out within the company. Customers were asked to participate in the survey. Hypotheses have been confirmed so it can be concluded that marketing activities are important and should be applied to them more attention. Another of the research was carried out a SWOT analysis. This analysis showed the potential of the company and the risks associated with market.
The influence of marketing activities on the image of company Diesel Service Hyclak
Keywords: Diesel; marketing; marketing-mix; analiza SWOT; ankieta; promocja; questionnaire; promotion; serwis; SWOT analysis